Design of a Novel Triple Band Monopole Antenna for WLAN/WiMAX MIMO Applications in the Laptop Computer - Jayshri Kulkarni; Raju Seenivasan; V. Abhaikumar; Deepak Ram Prasath Subburaj (International Journal of Antennas and Propagation)
This paper presents a triple band monopole antenna design with an overall size of 21  ×  8  mm2 for WLAN/WiMAX Multiple Input and Multiple Output (MIMO) applications in the laptop computer. It comprises of three monopole radiating elements, along with two rectangular open-ended tuning stubs. This structure excites 2.4/5.2/5.8 GHz WLAN and 2.3/3.3/5.5 GHz WiMAX bands. The prototype testing of proposed antenna array formed by using the same antenna design shows that, it has measured -10dB impedance bandwidth of 11.86% (2.22-2.50 GHz) in a lower band (fl), 5% (3.25-3.42 GHz) in medium band (fm) and 16.84% (5.00-5.92 GHz) in upper band (fu). The measured gain and radiation efficiency are well above 3.65 dBi and 75%, respectively, throughout the operating bands. Also, the measured isolation between two antennas is better than -20dB and envelope correlation coefficient (ECC) is less than 0.004 across the three bands of interest. This confirms the applicability of the proposed antenna array for MIMO applications in the laptop computer.